Efforts to Maximize the Performance of SMEs and Partnerships Through Experience and Business Capital - Junaidi Junaidi; Zulkarnain Lubis; Ihsan Effendi; Nasib Nasib; Ahmad Fadli (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The main objective of this study is to determine the direct and indirect effect of the variables of business experience and venture capital on the partnership and performance of SMEs. This type of research includes causal research. As for the population in the study, namely the SMEs fostered at PTPN III Nusantara, which amounted to 98 SME business actors. Where these 98 SMEs are all engaged in trading businesses. The sampling technique used was a saturated canoe. So that the sample in this study is 98 SME business actors. The data was collected using a questionnaire that was compiled based on each variable indicator item. The data analysis technique used Structural Equation Modeling with Smart PLS. The results of the study indicate that business capital directly has a significant direct effect on the partnership, while business experience is not significant. Furthermore, direct business experience, venture capital, and partnerships have a significant direct influence on the performance of SMEs. Lastly, only business capital indirectly has a significant influence on the performance of SMEs through partnerships, while business experience does not have an indirect effect.